2021
DOI: 10.1007/s00702-021-02369-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic drug-induced hyponatremia: results from a drug surveillance program–an update

Abstract: Hyponatremia (HN) is the most common electrolyte imbalance (defined as a serum sodium concentration Na(S) of  < 130 mmol/l) and often induced by drugs including psychotropic drugs. AMSP (Arzneimittelsicherheit in der Psychiatrie) is a multicenter drug surveillance program that assesses severe or unusual adverse drug reactions (ADRs) occurring during treatment with psychotropic drugs. This study presents data from 462,661 psychiatric inpatients treated in participating hospitals between 1993 and 2016 and ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…The prevalence of SIADH has been estimated to be as high as 11% in acutely ill psychiatric patients [ 14 ]. A drug surveillance program reported that the highest incidence of hyponatremia was found in antiepileptic drug users when compared to all other psychotropic drugs [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of SIADH has been estimated to be as high as 11% in acutely ill psychiatric patients [ 14 ]. A drug surveillance program reported that the highest incidence of hyponatremia was found in antiepileptic drug users when compared to all other psychotropic drugs [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Causality between antidepressants and hyponatremia was more frequently shown with SSRIs than with others. According to a drug surveillance program performed in Germany and Austria, SSRIs and SNRIs presented the highest risk of hyponatremia among antidepressants [ 48 ]. Of the SSRIs available, fluoxetine, paroxetine, and sertraline are the more common offenders.…”
Section: Hyponatremia Induced By Psychotropic Agentsmentioning
confidence: 99%
“…Oxcarbazepine is a keto-analog of carbamazepine and may be more associated with hyponatremia than carbamazepine [ 48 ]. Sachdeo et al investigated the mechanisms by which oxcarbazepine induces hyponatremia in epilepsy and healthy subjects [ 66 ].…”
Section: Hyponatremia Induced By Psychotropic Agentsmentioning
confidence: 99%
“…In clinical practice, however, the strength of association between opioids and SIADH does not appear to approach the magnitude of the association between SSRIs and SIADH [ 26 ]. Another class of drugs strongly associated with SIADH has been the anti-seizure drugs [ 27 ]. Carbamazepine and oxcarbazepine cause hyponatremia quite often [ 28 ].…”
Section: Siadh As An Adverse Drug Reactionmentioning
confidence: 99%